DIET CORRECTION OF GASTROINTESTINAL TRACT DYSFUNCTIONS OF INFANTS AFTER CEREBRAL ISCHEMIA - G.V. Yatsyk; I.A. Belyaeva; T.E. Borovik ("Paediatrician" Publishers LLC, 2007)
The article analyzes mechanisms of occurrence of gastrointestinal tract dysfunctions of infants after cerebral ischemia. It describes the clinical symptomatology of gastrointestinal impairment, particularly associated with vegetovisceral impairment, lactase deficiency, cow's milk protein intolerance. It gives recommendations about diet correction of gastrointestinal tract dysfunctions of infants. Key words: infants, gastrointestinal tract dysfunctions, dietotherapy.